2017
DOI: 10.1002/dvdy.24607
|View full text |Cite
|
Sign up to set email alerts
|

Zinc finger gene nolz1 regulates the formation of retinal progenitor cells and suppresses the Lim3/Lhx3 phenotype of retinal bipolar cells in chicken retina

Abstract: We conclude that Nolz1 has multiple functions during development and suggest a mechanism in which Nolz1 initially regulates the proliferation state of the retinal progenitor cells and then acts as a repressor that suppresses the Lim3/Lhx3 bipolar cell phenotype at the time of bipolar cell differentiation. Developmental Dynamics 247:630-641, 2018. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Genetic evidences for the GTPase and zinc finger transcriptional repressor encoding genes, gnl2 and znf503 (NOLZ1) as eye disorders-related genes are still missing but studies support their functional requirement for retinal developmental processes, including proper cell cycle exit of RPCs during RGC differentiation. 72,73 Notably, tubgcp4, gnl2 and znf503 were implicated in the regulation of cytokinesis late in mitosis. [71][72][73] This observation further indicates Atoh7 requirements for the regulation of cell cycle progression, at least in RPCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic evidences for the GTPase and zinc finger transcriptional repressor encoding genes, gnl2 and znf503 (NOLZ1) as eye disorders-related genes are still missing but studies support their functional requirement for retinal developmental processes, including proper cell cycle exit of RPCs during RGC differentiation. 72,73 Notably, tubgcp4, gnl2 and znf503 were implicated in the regulation of cytokinesis late in mitosis. [71][72][73] This observation further indicates Atoh7 requirements for the regulation of cell cycle progression, at least in RPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Single pairs of eyes were dissected from single embryos at 25,28,35,48,72, and 96 hpf and snap-frozen in liquid nitrogen, and stored at −80°C. Embryos older than 28 hpf were first anesthetized for 5-10 minutes in ethyl 3-aminobenzoate methanesulfonate (MS-222) (Sigma-Aldrich) in E3 medium.…”
Section: Eyes and Body Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3). This category contains 9 statistically significantly differentially expressed genes (including atoh7), which comprehend early expressed eye-field transcription factors (EFTFs, rx1 and six6a) [94][95][96][97] , stress response and extracellular matrix remodelling factors (hsp70.1, mmp14a) [98][99][100][101] , chromatin regulators (smarca5) 102 as well as microtubules organisers and cell cycle regulatory proteins (tubgcp4, znf503, gnl2) [103][104][105] . Other (albeit less significant) relevant biological processes emerging from this analysis were "cell cycle process" (GO:0022402), "chromatin remodeling" (GO:0006338) and "Wnt signaling pathway"…”
Section: Whole Mount Immunohistochemistrymentioning
confidence: 99%
“…Published studies have reported that Lhx3 is expressed in hindbrain, pineal gland, spinal cord, and pituitary (Seidah et al, ) as well as in retinal bipolar cells (Balasubramanian, Bui, Ding, & Gan, ; Blixt, Konjusha, Ring, & Hallbook, ; Elshatory et al, ) and the inner ear (Huang et al, ; Hume, Bratt, & Oesterle, ; Rajab et al, ). Deletion of the two LIM domains and a part of the HD of LHX3 by conventional knockout approach in mice leads to abnormal Rathke's pouch and embryonic death at birth or neonatal death within 24 h after birth and abolishes the expression of Pit‐1 , TSH , GSU , and GH (Sheng et al, ).…”
Section: Introductionmentioning
confidence: 99%